Pemberdayaan Keluarga Lansia melalui Program Bina Keluarga Lansia (BKL): Literature Review - Yuniar, Adinda Ragil; Huda, MIftahul; Masajida, Nadyalis Ta'mara; Andyastanti, Tisnalia Merdya (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
The Central Statistics Agency in 2023 shows that the number of an elderly people in Indonesia had growth. Elderly people are included in the population at risk because the elderly population is vulnerable to their health and has a higher chance of spreading the disease they experience. Quality of life of an elderly can be affected from health status that has been decreased. The government through the National Population and Family Planning Agency (BKKBN) created an Elderly Family Development (BKL) program in order to improve the health quality of the elderly people. The purpose of writing this article is to discover the implementation of the BKL program in Indonesia. The method of this article is literature review. Reference articles were collected via Google Scholar, Garuda, and Publish or Perish software using the keywords quality of life for the elderly; fostering elderly families; and implementation of BKL. Result of the literature review that has been carried out, it can be seen that the implementation of the Elderly Family Development (BKL) program is in accordance with the guidelines provided.